Influences of international agricultural trade on the global phosphorus cycle and its associated issues. (July 2021) - Lun, Fei; Sardans, Jordi; Sun, Danfeng; Xiao, Xiao; Liu, Ming; Li, Zhuo; Wang, Chongyang; Hu, Qiyuan; Tang, Jiayue; Ciais, Philippe; Janssens, Ivan A.; Obersteiner, Michael; et al.
Highlights: International agricultural trade strongly redistributed global P cycle. Global agricultural P trade represents a fraction of 16% of P in harvested crops. 1/3 of global virtual P fertilizer flows were associated with global soybean trade. Global crop trade saved 0.2 Tg P y -1 of P fertilizers globally. Abstract: Industrial phosphorus (P) fertilizer has substantially improved global food production, but has also led to environmental impacts. Intensive global agricultural trade has increased and the impacts of trade on aggravating or alleviating future P scarcity must be examined, especially for the most vulnerable countries. We combined data to estimate the global P trade among countries and its impacts on global P flows, based on global agricultural trade, cropland soil P budgets and crop P fertilizer footprints (the amount of industrial P fertilizer applied for producing one unit of P in the harvested crop). The global agricultural P trade represented a fraction of 16% of P in harvested crops in 2014, half of which was exported from the United States of America, Brazil and the European Union and one fifth imported by China. Virtual P fertilizer flows (about 2.60 Tg P y -1 ) referred to industrial P fertilizers applied to traded crops by exporting countries; thus, 1/3 of global virtual P fertilizer flows were associated with the international soybean trade. P use efficiency (PUE), the ratio of the harvested crop-P to the total external P inputs, is a larger problem for tropical than temperate countries. Global crop trade had brought in a net 0.2 Tg P y -1 savings of industrial P fertilizers globally, compared to crop production in export and import countries. >0.50 Tg y -1 of the gross global accumulation of soil P and P in freshwater were associated with global agricultural trade. Global PUE, however, could be improved considerably, and thus global cooperation and improving PUE could help to solve the problem of future P scarcity. Vulnerable countries should also propose urgent national plans to address their own situations of P scarcity or low PUE.